1998
DOI: 10.1161/01.res.83.10.986
|View full text |Cite
|
Sign up to set email alerts
|

Sox4-Deficiency Syndrome in Mice Is an Animal Model for Common Trunk

Abstract: Embryonic mice lacking functional Sox4 transcription factor die from cardiac failure at embryonic day (ED) 14. Heart morphogenesis in these embryos was analyzed in hematoxylin-azophlochsin or immunohistochemically stained, 3-dimensionally reconstructed serial sections between ED12 and ED14. Although Sox4 is expressed in the endocardially derived tissue of both the outflow tract and atrioventricular canal, Sox4-deficient hearts only suffer from defective transformation of the endocardial ridges into semilunar v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(75 citation statements)
references
References 43 publications
5
70
0
Order By: Relevance
“…2K,L, 3K,L, 4K,L). Runx2 plays an important role in epithelial HMG-box transcription factor Ya et al, 1998 to mesenchymal transformation during tooth formation and in the development of osteoblasts, processes in which TGF␤ signaling has been implicated. Runx2 may be an downstream effector of TGF␤ signaling (Lee et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…2K,L, 3K,L, 4K,L). Runx2 plays an important role in epithelial HMG-box transcription factor Ya et al, 1998 to mesenchymal transformation during tooth formation and in the development of osteoblasts, processes in which TGF␤ signaling has been implicated. Runx2 may be an downstream effector of TGF␤ signaling (Lee et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies revealed that the mutation of Sox-4(Sox-4 -/-) in the embryo of mice leads to premature death at 14th embryonic days due to impaired development of the endocardial ridges (Schilham et al, 1996: Ya et al, 1998. In 1998, Southard-Smith et al reported that premature termination of Sox-10, a member of the Sox family, disrupted neural crest development due to apoptosis in Dom Hirschsprung mouse models.…”
Section: Discussionmentioning
confidence: 99%
“…Many Sox (SRY-HMG box containing) proteins are assumed to be involved in the regulation of developmental stages of several distinct tissues (Uwanogho et al, 1995: Schilham et al, 1998: Southard-Smith et al, 1998 and nervous system in mammals (Prior andWalter, 1996: Jay et al, 1997). Unlike other Sox family proteins, Sox-4, a transcription factor, contains serine-rich trans-activation domain in the C-terminus and is selectively expressed in brain, heart and testis of fetus mice (van de Wetering et al, 1993: Schilham et al, 1997.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that the SOX4 molecular activity during caracinogenesis is influenced by additional factors that are enriched in a tissuespecific manner. The requirement for SOX4 in a wide range of developmental processes (van De et al, 1993;Ya et al, 1998;Cheung et al, 2000) further argues for a synergy between SOX4 and tissue-selective partner proteins. Among the identified highly upregulated genes in intrahepatic liver tumors, SOX4 was an attractive candidate for further investigation.…”
Section: Identification Of Genes Associated With Intrahepatic Metastamentioning
confidence: 99%